Word Play in Georges Brassens - Hodgson, John William (My University, 1977)
A discussion of the techniques used by Georges Brassens in his songs to make plays on words and phrases.
Keywords: Romance Languages; Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures